(untitled) (Architecture Image Studies, 2025)
The implementation of the digital economy in Bandung City reflects the synergy between entrepreneurship and technology in driving economic growth. As a creative city, Bandung has leveraged digital technology to strengthen its strategic sectors. Economic acceleration follows an approach adapted from the IMF, ADB, and G20, with operational adjustments tailored to local conditions. Sector analysis is conducted using qualitative techniques with nominal or ordinal scales to measure qualitative variables. Clustering and ranking methods are applied to categorize sectors based on specific criteria, facilitating the identification of priority interventions. The findings indicate that the information and communication sector serves as the primary driver of economic growth in Bandung City. Additionally, the city demonstrates strong MSME diversification, particularly in the food, beverage, and fashion industries. This diversification enhances the resilience of MSMEs against economic crises. Although most MSMEs remain micro-scale with low income levels, they possess growth potential if supported by appropriate policies. The adoption of digital technology has progressed rapidly in marketing and payment systems; however, its application in production and design remains limited and requires further development to enhance business competitiveness.